Street-Level Workers and the Construction of Social Infrastructure in Suburban Neighbourhoods - Kuoppa Jenni; Kymäläinen Päivi (Cogitatio, 2023)
The article examines the provision of social infrastructures in suburban neighbourhoods from the perspective of street-level workers. The concept of infrastructure is usually related to material and structural conditions but can equally apply to social infrastructures that are continuously constructed and maintained in social practices. These social infrastructures are embedded in structures and social arrangements and are related to past decisions. Our research focuses on the social infrastructures of two high-rise suburbs in Finland, built in the 1960s and 1970s. Since the 1990s, these neighbourhoods have experienced socioeconomic decline and transformation into a multicultural milieu. While suburbs have often been overlooked in urban politics and public discourses, a wide range of social infrastructures have also evolved in these districts and are continuously maintained. The main research data consists of interviews with street-level workers who participate in the production of such local social infrastructures. The article identifies and analyses the essential factors and preconditions as well as the challenges and contradictions of the provision of social infrastructure in these suburban contexts. This understanding is needed in order to foster an extensive social infrastructure and to deter counterforces from exacerbating socio-spatial inequalities and social polarisation in cities.